Effect of inorganic selenium on reproductive performance of Large White Yorkshire gilts - GNANARAJ, P TENSINGH; SIVAKUMAR, T; ARUNACHALAM, S; SUNDARAM, S MEENAKSHI; RAMESH, V (The Indian Journal of Animal Reproduction, 2023)
A study was carried out to find out the influence of dietary selenium on the reproductive performance of gilts at Swine Breeding Unit, Livestock Research Station. Tamil Nadu. Twenty four Large White Yorkshire gilts, at breeding age, were randomly allotted to three groups of eight gilts each. The dietary treatments groups were 0.1 ppm of Se. 0.3 ppm of Se and control diet devoid of Se. Dietary supplementation of selenium at 0.1 ppm and 0.3 ppm resulted significantly (P<0.0 I) higher mean litter size at birth and weaning than control. Similarly. differences in mean birth weight was significantly (P<0.05) higher ( 1.30 ± 0.06 kg) at 0.3 ppm compared to 1.23 ± 0.07 kg in 0.1 ppm selenium and a very poor weight of I. IO± 0.04 kg in control. The mortality rate remained significantly (P<0.05) lower in 0.3 ppm (8.23 ± 3.12) and 0.1 ppm selenium groups (10.87±3. 18). There were highly significant (P<0.0 I) reductions both in SGOT and SGPT activity at gestation and lactation stages by selenium supplementation irrespective of the levels.